The female image in Eugene O´Neill´s Desire under the elms and A moon for the misbegotten - Pacheco, Gilda (Revista de Filología y Lingüística de la Universidad de Costa Rica, 2015)
El siguiente artículo analiza el papel de la mujer en dos obras escritas por el dramaturgo estadounidense conocido Eugene O’Neill. Estas obras son Deseo bajo los olmos y una luna para el bastardo. Luego, los personajes de Abbie Putnam y Josie Hogan respectivamente se estudian bajo un ámbito feminista que exhibe la falta de identidad femenina, un rasgo recurrente de las obras de O’Neill. The following article analyzes the female role in two plays written by the well-known American playwright Eugene O’Neill. These works are Desire Under the Elms and A Moon for the Misbegotten. Then, the characters of Abbie Putnam and Josie Hogan respectively are studied under a feminist scope that exhibits the lack of female identity, a recurrent trait of O’Neill’s plays.